AquaMMapS: An Alternative Tool to Monitor the Role of Water Molecules During Protein–Ligand Association. (25th January 2018) - Cuzzolin, Alberto; Deganutti, Giuseppe; Salmaso, Veronica; Sturlese, Mattia; Moro, Stefano
Abstract: Unquestionably, water appears to be an active player in the noncovalent protein–ligand binding process, as it can either bridge interactions between protein and ligand or can be replaced by the bound ligand. Accordingly, in the last decade, alternative computational methodologies have been sought with the aim of predicting the position and thermodynamic profile of water molecules (i.e., hydration sites) in the binding site using either the ligand‐bound or ligand‐free protein conformation. Herein, we present an alternative approach, named AquaMMapS, that provides a three‐dimensional sampling of putative hydration sites. Interestingly, AquaMMapS can post‐inspect molecular dynamics (MD) trajectories obtained from different MD engines using indifferently crystallographic or docking‐driven structures as a starting point. Moreover, AquaMMapS is naturally integrated into supervised molecular dynamics (SuMD) simulations, presenting the possibility to inspect hydration sites during the ligand–protein association process. Finally, a penalty scoring method, named AquaMMapScoring(AMS), was developed to evaluate the number and nature of the water molecules displaced by a ligand approaching its binding site during the binding event, guiding a medicinal chemist to explore the most suitable regions of a ligand that can be decorated either with or without interfering with the interaction networks mediated by water molecules with specific recognition regions of the protein. Abstract : Water watch : The AquaMMapS tool was developed to individuate zones occupied by stationary water molecules during MD simulations. Individuation of stationary water voxels in a protein binding site can be exploited for drug design. AquaMMapScoring was developed to evaluate the penalty associated with different ligand substituents, considering electronegativity and capability of forming hydrogen bonds and stability of the water displaced.